Antibiotic-sparing strategies for multidrug-resistant organism (MDRO) infections - Geng, Shuai; Tang, Qing; Shi, Ning (Frontiers in Pharmacology, 2025)
The global rise of multidrug-resistant organisms (MDROs), such as carbapenem-resistant Enterobacteriaceae (CRE) and methicillin-resistant Staphylococcus aureus (MRSA), has rendered conventional antibiotics increasingly ineffective, particularly in intensive care units (ICUs) where mortality rates exceed 50% in severe infections. Overuse of broad-spectrum antibiotics accelerates resistance while disrupting host microbiota, necessitating innovative “antibiotic-sparing” strategies. This review synthesizes three pillars of intervention: (1) non-antibiotic therapies, including bacteriophages for targeted pathogen lysis, monoclonal antibodies (e.g., BiS4αPa against Pseudomonas aeruginosa), and nanotechnology-enhanced antimicrobial peptides (AMPs) for biofilm disruption; (2) antimicrobial stewardship integrating rapid diagnostics (MALDI-TOF, mNGS), PK/PD-guided dosing, and short-course regimens (7-day therapy validated by RCTs); and (3) transmission prevention through UV-C disinfection, AI-driven hygiene compliance, and gut microbiota modulation. Key innovations include phage-antibiotic synergies, bispecific antibody engineering, and dynamic PK/PD-TDM frameworks. Despite challenges in clinical translation and cost-effectiveness, these strategies collectively reduce antibiotic reliance, mitigate resistance evolution, and offer a paradigm shift toward precision infection control. Future directions emphasize combinatorial therapies, regulatory harmonization, and scalable environmental-behavioral interventions to address the post-antibiotic era crisis.